(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the results of the population’s knowledge about a healthy lifestyle, which was carried out through questionnaires and interviews. 167 people aged 16 to 80 years in the Namangan region of the Republic of Uzbekistan took part in the survey and interviews. The survey was conducted using a questionnaire consisting of 15 questions about a healthy lifestyle. From the results of the study, it follows that many people do not follow a healthy lifestyle, and also do not have a specific concept of a healthy lifestyle. To inform the population about a healthy lifestyle, it is necessary to conduct information campaigns, educational programs, and sporting events. Increasing public knowledge about healthy lifestyles is important and should be a public health priority.